Broadband nonlinear absorption properties of two-dimensional hexagonal tellurene nanosheets. Issue 36 (11th September 2019) - Zhang, Fang; Liu, Guowei; Wang, Zhengping; Tang, Tianhong; Wang, Xinle; Wang, Chaowei; Fu, Shenggui; Xing, Fei; Han, Kezhen; Xu, Xinguang
Abstract : Low saturable intensity, large TPA coefficient and the absorption cross-section demonstrate that tellurene is an advanced broadband nonlinear absorption material and has potential applications in the nonlinear optics field, especially in the infrared band. Abstract : Two dimensional (2D) Group-VI Te, tellurene, was successfully exfoliated using a liquid phase exfoliation (LPE) method. The prepared tellurene nanosheets possessed a thickness of 4.3–4.6 nm and the lateral dimension ranged from hundreds of nanometers to several microns. The broadband nonlinear absorption properties were explored for the first time (as we know) using a z -scan method with the laser photon energy in the range of 0.73–2.76 eV, corresponding to the near-infrared-visible waveband. Tellurene nanosheets exhibited excellent broadband saturated absorption and optical limiting behaviors. The low saturable intensity and the large modulation depth for saturated absorption with low energy photon excitation highlight the superiority of the infrared band as a saturable absorber. In addition, with large energy excitation, tellurene manifested an apparent two photon absorption behavior in the visible band, thus it can be used as an optical limiting material. By adopting the mode-locking technique, this high-quality saturable absorber can be applied in all-solid-state or fiber lasers to generate ultra-short and ultra-high peak power laser pulses. Meanwhile, tellurene as an optical limiting material can protect the sensitive optical devices and human eyes. So, our work not only demonstrates that tellurene is a promising broadband nonlinear optical material, but also implies its application prospects in optics.